A festa em nós: fluxos, coexistências e fé em Santos Reis no Distrito de Martinésia Uberlândia/MG - Marques, Luana Moreira (2011)
The popular celebrations are social structures that reproduce beliefs, symbols and values and are permeated by the exchanges and the realization of man as a social subject. In that space-time the volunteers and spectators are and stay together, sharing practices and collective symbols. In Brazil´s interior are still some cultural events, such as Festas de Santos Reis. In general, this type of festival has permeated the traditional reproduction by modern practices. Considering the dynamics, changes and adaptations of Festa de Santos Reis through time and space, it was established as a case of study at Martinésia District located in Uberlandia, Minas Gerais, Brazil. The evolution of the feast in this place was imbued with new values, movements, objects and subjects, in the same time that left part of their practices and representations. Therefore, this study aimed, mainly, to investigate such dynamics and understand its consequences in place and how their subjects perceive the issue metamorphosis. For this to happen, there were incursions into the field between the years 2009 and 2011, with emphasis on effective participation, collect of interviews and application of questionnaires during the 2010 and 2011 feasts. The readings and theoretical reflections helped the understanding of the lived, allowing deconstructs preconceived ideas and rethink the festival while social flow that are reproduced in the place. From the theoretical and empirical experience, it was verified that Festas de Santos Reis realized in Martinésia are fluid structures, composed of multiple subjects that, in its multiplicity, produce the real thing, even amid the spectacle. The smells, colors, smiles and flavors experienced never repeats, because the flow does not allow that the practices, expressions and elements be identical. From this perspective, the popular celebration changes daily, as the subject is creature of transformation. It forms a unique organism that combines the passenger and the tradition, the flow and the fixed - all of which intertwine the subject and allow the movement of culture. Thus, it is understood that the festivals are expressions of social life and transmuted, resignify and adapt according to the needs and claims of its subjects at the time and space that exists.